Effect of dietary T-2 toxin levels on liveability, organs weight, immunity and histopathology of organs in Japanese quails - SINGH, RAM (The Indian Journal of Animal Sciences, 2021)
To establish the tolerance level of T-2 toxin, day-old Japanese quail chicks (n=225) were divided into five dietary treatments: T1, control; T2, T1+50 ppb T-2 Toxin; T3, T1+100 ppb T-2 Toxin; T4, T1+150 ppb T-2 Toxin; T5, T1+200 ppb T-2 Toxin. Each diet was fed to 3 replicated groups of 15 birds each from 1 to 35 days of age. The results showed that the overall liveability percentage, at fifth week of age in T1 was statistically similar to T2 and T3; and higher than T4 and T5. The relative weight of liver, kidney and spleen in T1 was lower than T4 and T5; and statistically similar to T2 and T3. The relative weight of bursa in T1 was higher than T4 and T5; and statistically similar to T2 and T3. The CMI and HA titre values in T1 was higher than T4 and T5. The CMI and HA titre value in group T1 was statistically similar to T2 and T3. In group T2, mild necrosis of mucosa in the proventriculus and gizzard and in T3, dystrophy and granular degeneration in the liver and kidney and necrosis of mucosa in the gizzard and proventriculus was observed. In T4 and T5, severe histopathological lesions including hepatocyte necrosis with discrete foci, necrosis and inflammation of gallbladder mucosa having mild proliferation of bile ductules, necrosis of intestinal epithelium following transient shortening of villi and mitotic figures in crypt epithelium; necrosis in feather epithelium and mucosa of the proventriculus and gizzard was observed. In addition, dystrophy and granular degeneration in the liver and kidney; interstitial nephritis, kidney sclerosis and glomerulonephritis was also observed. It was concluded that Japanese quails can tolerate up to 100 ppb of T-2 toxin in their diet without any adverse effects on their liveability percentage, organs weight, immunity and histopathology of organs during 0-5 weeks of growth period.